Adolescent tobacco use and health in Southeast Asia - Al-Sadat, Nabilla; Misau, A.Y.; Zarihah, Z.; Dahlui, Maznah; Tin, Tin Su (SAGE Publications, 2010)
The use of tobacco by adolescents is a major public health concern worldwide. There are 1.2 billion smokers globally, of which more than 50 are young people. The Southeast Asian countries have about 600 million tobacco smokers within the global burden of tobacco users. Most smokers begin at early stage of life and persist through adulthood. Malaysia alone has about 5 million smokers, 20 of whom are younger than 18 years old. Many factors are implicated in the continuous rising trend of tobacco use among adolescents in Southeast Asia. A triad of family, environmental, and individual factors synergistically acts to motivate adolescents toward smoking. This article discusses the current trends of tobacco use and implications of increasing rise in adolescent smoking in the Southeast Asia region.